Comparative Blood Chemistry of Hybrid Catfish (Clarias gariepinus x C. macrocephalus) Infected with Aeromonas hydrophila to those Non-infected with A. hydrophila - Koeypudsa, Weena; Jongjareanjai, Malinee; Phalitakul, Sukanya; Punnarak, Porntep (Journal of Mahanakorn Veterinary Medicine, 2020)
Hybrid catfish (Clarias gariepinus x C. macrocephalus) was purchased from the private farm at 12.2 ± 1.1 cm total length and 11.2 ± 3.1 g body weight. All catfish were divided into 4 groups as following: low water temperature (19 - 20OC) for 1 day experiment (Lt1d), low water temperature for 4 days experiment (Lt4d), high water temperature (29 - 30 OC) for 1 day experiment (Ht1d) and high water temperature for 4 days experiment (Ht4d). Each group composed of infected and non-infected catfish. Non-infected catfish was intra-peritoneal injection with 0.1 ml normal saline. All infected catfish were 0.1 ml Aeromonas hydrophila intra-peritoneal injection which lethal doses were 30, 50 and 90% fished killed: LD30, LD50 and LD90. The concentrations of bacteria were 2.5 x 103 - 5.1 x 106 colony forming unit (cfu)/ml for 2 groups of low water temperature (Lt1d and Lt4d) but 2.8 x 103 - 1.4 x 109 cfu/ml for 2 groups of high water temperature (Ht1d and Ht4d). Blood was randomly taken from sedated fish to investigation and interpretation of catfish health. Blood chemistry parameters were serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), blood urea nitrogen (BUN), creatinine (Cr), alkaline phosphatase (ALP) and hematocrit (Hct). Blood chemistry values revealed that infected fish causes blood changes owing to A. hydrophila infection. These results interpret to the damages of liver (SGOT, SGPT and ALP), anterior kidney (Hct) and posterior kidney (BUN, Cr and ALP). Furthermore, changes of ALP and Hct showed that infected fish were in stress situation. Catfish from bacterial infection groups will experience to anemia and lead to hypoxia because of low Hct. The obtained data are very useful to provide blood parameters which enable early detection of mass mortality caused by bacterial infection.